Dual model sensors for viral RNA and protein detection for SARS- CoV-2 in saliva - Ma, Xuanye (Cranfield University, 2023)
The coronavirus disease 2019 (Covid-19) pandemic emerged as an infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) over the past 3 years, causing enormous threats to humans and economic loss. It was reported that currently, nearly 68% of the population shows a degree of immunity to the disease. Though vaccine has played a critical role to protect the population, people are at risk of second or third infections with fading antibody titers against the virus. The detection of the viral load was crucial for monitoring the spread of this disease, and the detection of the antibody concentration to the virus was significant as well to understand the neutralization activity and vaccine response. This thesis reports the development of a rapid paper-based platform, which provides nucleic acid detection and immunoassay to test both active infections and body immunity. The project focused on a non-invasive sample, human saliva, as an alternative to nasopharyngeal swabs for diagnosis. The nucleic acid test, employing reverse transcription loop-mediated isothermal mediated amplification (RT-LAMP), was further integrated into a novel paper microfluidic platform, where the result could be reported within 30 mins. Under the optimized conditions, RT- LAMP assay correctly detects above 135 copies µL⁻¹ of synthetic SARS-CoV-2 sequence. Moreover, a paper-based immunoassay was devised and constructed, following meticulous refinement of detection parameters and comparative analysis against a conventional 96-well plate assay for the identification of immunoglobulin G (IgG) targeting the SARS-CoV-2 spike protein. For the paper- based immunoassay, the dynamic range of the IgG was 0.5 μg mL⁻¹ to 50 μg mL⁻¹ , which was sensitive enough compared to clinical values. It should be noted that only commercially available artificial saliva was utilized to test the analytical performance of the developed assay. In conclusion, these results demonstrated a rapid and easy-to-use paper microfluidics platform with the potential to be further implemented as a comprehensive detection tool for monitoring both pathogenetic infection and immune levels.
Chianella, Iva - Associate Supervisor
Keywords: COVID-19; nucleic acid; antibody concentration; point-of-care diagnosis; rapid paper-based platform; reverse transcription loop-mediated isothermal mediated amplification (RT-LAMP)